Pemberdayaan Perempuan dalam Memperkuat Perekonomian Keluarga Melalui Pemanfaatan Banner dan Google Maps Sebagai Media Promosi Umkm di Desa Menanti Selatan, Kecamatan Kelekar, Kabupaten Muara Enim: Penelitian - Jimmy Rimba Rogi; Fitriani; Yesiana; Reni; Denissa Sundari; Cantika; Tiara Canesha (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Women in rural MSMEs face promotion and digital literacy constraints despite significant family economic contributions. This study analyzes empowerment effectiveness through banners and Google Maps to enhance visibility and marketing reach for women MSMEs in Menanti Selatan Village. Employing participatory descriptive qualitative KKN-based approach, population comprised 50 women MSME actors with purposive sample of 15 active businesses. Instruments included observation sheets, semi-structured interviews, and visual documentation, analyzed via thematic data reduction and source triangulation. Findings reveal banners improved visual identity and consumer trust, while Google Maps expanded online access and digital literacy. The program also boosted entrepreneurs' confidence. It is concluded that conventional-digital media integration sustainably empowers women's economy